A hybrid and hsa for enhancing a multilayer perceptron learning [electronic resource] - Abdirashid Salad Nur, 1982-; Siti Mariyam Shamsuddin, supervisor; Nor Haizan Mohamed Radzi (2014)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia,2014